Pemikiran Karl Marx Tentang Struktur Masyarakat - kambali, muhammad (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2020)
This research is a library research (liberary research), data collected by researchers from secondary sources. This research aims to reveal Karl Marx's thoughts about superstructure and infrastructure dialectics in the structure of society. The data were analyzed by researchers using the content analysis method. The results of the study stated that according to Karl Mark, the community structure was divided into two major parts, namely infrastructure (base) and superstructure (superstructure). The lower layer (infrastructure / base) is determined by two things, namely the productive forces (productivkrafte) and production relations (production sverbalt-nisse). The components that make up the productive forces consist of work tools, the ability and experience of society in work (labor), and the technology used in the production process. Meanwhile, the superstructure consists of 2 types, namely the institutional order and the order of collective consciousness or the building of ideology. Institutional arrangements are all kinds of institutions that regulate community life outside the field of production, which includes market organization, education system, public health system, law and the state. Meanwhile, the order of collective consciousness is an order that contains a belief system, norms and values ​​that provide a framework for understanding, meaning and spiritual orientation. The content of this collective consciousness order consists of world views, religion, philosophy, societal morality, cultural values ​​and arts